Cancer Diagnostics: Quantitative and Specific Detection of Exosomal miRNAs for Accurate Diagnosis of Breast Cancer Using a Surface‐Enhanced Raman Scattering Sensor Based on Plasmonic Head‐Flocked Gold Nanopillars (Small 17/2019). Issue 17 (25th April 2019) - Lee, Jong Uk; Kim, Woo Hyun; Lee, Hye Sun; Park, Kyong Hwa; Sim, Sang Jun
Abstract : In article number1804968, Kyong Hwa Park, Sang Jun Sim, and co‐workers develop a surface‐enhanced Raman scattering (SERS)‐based ultrasensitive exosomal miRNA detection platform with single‐nucleotide specificity, obtained by enhanced SERS signals from uniform plasmonic head‐flocked gold nanopillar SERS substrate that generates self‐assembled hot spots and enables hybridization between short oligonucleotides (i.e., miRNAs and locked nucleic acid probes).